SAHNYA PERKAWINAN MENURUT UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DITINJAU DARI HUKUM PERJANJIAN - Trusto Subekti (Jurnal Dinamika Hukum, 2010)
Legal certainty is an indicator for a legal into good legal category, the fact about  the validity of marriage has led a multi interpretation among the experts and the society, especially among Muslims. This is shown in the society members statement that "the secret marriage" as a valid marriage according to religious even it is not listed. " Arranged marriage in a society is intended to solve problems within the scope of family law and marriage, not to create new problems in society. the problem is how the legitimacy of the marriage law seen from the viewpoint of the agreement, with expectations  to obtain certainty about the right interpretation of the validity of marriage, so the confusion about the validity of a marriage can be resolved. Seen from the viewpoint of the legal agreements, Marriage included in family laws agreements and according to the provisions this agreements are categorized as a formal agreements, it means that the agreement was born and legally binding if the requirements and procedures (formality) of marriage according Act No. 1 Year 1974 jo. No PP. 9 Year 1975 fulfilled. Afterwards, from the binding aspect, the function of marriage records juridically is a requirement in order to obtain recognition and protection from the state and binding the third party: (others). According to the regulatory aspects the procedure and the registration of marriages reflect a legal certainty, as the result the existence of marriage proved by  a marriage certificate.As a further consequence, in the law viewpoint a marriage is invalid if the marriage did not comply the procedure and registration of marriage.Keyword: Validity of marriages, Law Agreement